Religion and the Market: Opposition, Absorption, or Ambiguity? - Haddorff, David W. (Review of Social Economy, 2000)
This article addressed the complex relationship between religion and the market by proposing three basic paradigms, and then applying them to contemporary Christian social thought (or social ethics). The first conflicting model, following Max Weber and Karl Marx, views religion and the market in opposition, which results in greater secularisation. The second, following Emile Durkheim, proposes a 'functionalist' model of society, in which the market itself becomes sacred. The third, following Karl Polanyi, claims the two are more dialectical, in that both are affected by the power of the other; they remain in an ambiguous relationship. The author argues that the third model is the most coherent description of this complex relationship as well as the one most consistent with the convictions of Chrstian social thought.
Keywords: church & state; dialectical; double movement; dystopian; economics; functionalism; hom. economics; homo economicus; religious aspects; secularisation; secularization; social ethics

Rural Community Life and the Importance of Reciprocal Survival Strategies - Meert, Henk (Sociologia Ruralis, 2000)
Although Belgian poverty is mainly concentrated in urban regions, the profound restructuring of labour and food markets, the dismantling of the welfare state and the growth of new types of households are also producing poverty and social exclusion in rural areas. This paper stresses that not every deprived rural household should be regarded as excluded from society. By developing survival strategies, households attempt to escape from social marginalization. To understand these responses, a typology of survival strategies is constructed, based on Polanyi’s spheres of economic integration (market exchange, redistribution and reciprocity). These survival strategies, including agricultural and non-agricultural activities, are analysed in relation to the Hageland,a peripheral rural area in Flanders. Based upon Doreen Massey’s geological metaphor, the current potentials and obstacles embedded in the historical layers of the socio-spatial structure of the area, are assessed. By comparing the results of this research with similar research amongst urban households, some particularities of rural poverty are distinguished.
Keywords: Belgium; economic integration; poverty; urban poverty

Interpreting the Consequences of Midwestern Agricultural Industrialization - King, Martin Burce (Journal of Economic Issues (Association for Evolutionary Economics), 2000)
The article focuses on the interpretation of consequences of Midwestern agricultural industrialization. The nature and consequences of the industrialization of agriculture are well documented in academic research and in the popular press. Interpretations of the process vary in reflection of the diverse perceptions of the nature and overall significance of industrialization. Suggested policies range from a "hands-off" to a "prohibit and prevent wherever possible" approach. Both approaches are unrealistic because they fail to recognize the historical context in which agricultural industrialization is taking place. In this paper, the author presents a historical context for the process, using nineteenth-century Illinois and the industrialization of swine production as examples of commercialization and industrialization of Midwestern agriculture, respectively. The author integrates the work of Karl Polanyi and K. William Kapp into the discussion to provide a foundation for realistic policy and to demonstrate the relevance of an institutionalist perspective to the formation of contemporary agricultural policy.
Keywords: KAPP, Karl William; agriculture; commercialization; crop insurance; economic theory; evolutionary economics; industrialization; production (economic theory); rural industries

A Tale of Three Karls: Marx, Popper, Polanyi and Post-Socialist Europe - Marquand, David (Royal Institute of Philosophy Supplement, 2000)
Focuses on the social and political changes brought about by capitalism in Europe. Advocacy of socialist Karl Marx, Karl Popper and Karl Polanyi for social democracy; Discussion on the relationship between society and economy; Notion of futurism regarding the inevitability of change.
Keywords: Europe; European politics & government; capitalism; change; socialism

The Second Great Transformation: The Politics of Globalisation in the Global North - Zincone, Giovanna; Agnew, John (Space & Polity, 2000)
Dominant strands of thinking in contemporary social science consider economic globalisation, the increasing role of cross-border flows and transactions in economic organisation, in terms of some combination of either limited or considerable economic impact and either positive or negative consequences for the general welfare. Little attention has been given thus far to its political consequences within those parts of the world, the developed countries of the Global North, where its impact should be greatest. This paper argues that economic globalisation is in fact the geographical face of a new great transformation in the forces of production (reductions in transport and communication costs, dramatically increased capital and labour mobility, delocalisation of technological innovation, etc.) on a par in its potential impact with the transition to market society with fragmented states first identified by Karl Polanyi. Globalisation, it is claimed here, is the product of action by states as much as markets and, in the short-term, seems to accentuate social inequalities within states, to weaken the rights of current citizens, to lessen the weight of the democratic vote and to stimulate a profound restructuring of both work and the welfare state in the developed world or ‘Global North'. But more significantly, in the long term, when focus on globalisation shifts from its recent economic causes and short-term political impact to its more long term political consequences, recent trends towards a more global economy can be seen in a different light: as entailing a potential positive transformation in the geographical organisation of political rights and citizenship on a par with the first great transformation in economic life and citizenship signalled by the coming of market society.
Keywords: globalization; international economic relations; market society; political science; production (economic theory)

Sustainable Agriculture in the United States and France: A Polanyian Perspective - Barham, Mary Elizabeth (2000)
Keywords: France; social movements; sustainable agriculture

Three Pillars of Welfare State Theory: T.H. Marshall, Karl Polanyi and Alva Myrdal in Defence of the National Welfare State - Holmwood, John (European Journal of Social Theory, 2000)
Current social and political theory is sceptical of the future of welfare states in the face of global markets. Their moral claims, too, have been challenged by the neo-liberal association of market capitalism and individual freedom and by an implicit acceptance of that critique - of the welfare state as bureaucratic - by left-wing commentators. This article offers a defence of the national welfare state as the guarantor of 'complex freedom'. This defence is derived from the theoretical contributions of Marshall, Polanyi and Myrdal and offers a reconsideration of the debate immediately after the second world war over the welfare state and its relevance today. Marshall's concept of social rights has become a familiar part of our own debate, but it is argued that Polanyi provides the rigorous critique of market relationships which is missing, and Myrdal locates gender issues as central to the understanding of welfare state development and women's rights as integral to social rights.
Keywords: economic policy; gender; globalization; government policy; human rights; markets; public welfare; social & economic rights; social rights; welfare; welfare economics

The Great Transformation - Brand, Horst (Dissent (00123846), 2000)
The article reviews the book "The Great Transformation: The Political and Economic Origins of Our Time," by Karl Polanyi.
Keywords: Great Transformation, The (Book); book review; economics; nonfiction

Conceptualizing Resistance to Globalization - Chin, Christine B. N.; Mittelman, James H. (Globalization and the Politics of Resistance, 2000)
Assessments of resistance to globalization are necessarily influenced by the manner in which one conceptualizes these processes. Too often, both of the terms (‘resistance’ and ‘globalization’) are used promiscuously, the latter as a buzzword or catchall and the former in many different ways, sometimes as a synonym for challenges, protests, intransigence, or even evasions. Hence, we seek to juxtapose alternative explanations of resistance and highlight the complexities of conceptualizing it. The purpose of this chapter, then, is to explore the question, what is the meaning of resistance in the context of globalization?
Keywords: Islamist movement; NAFTA; globalization; international political economy; organic intellectual; resistance; symbolic resource; transnational capital

The Reproving of Karl Polanyi - Hejeebu, Santhi; McCloskey, Deirdre (Critical Review, 2000)
Karl Polanyi's The Great Transformation has had enormous influence since its publication in 1944. In form, this influence has been salutary: Polanyi targets one of the main weaknesses of modern economics. But in substance, Polanyi's influence has been baneful. Mirroring the methodological blindness he criticizes, Polanyi insists on the all-or-nothing existence/nonexistence of laissez faire--and on its all-or-nothing goodness/badness.
Keywords: critique; history of economic thought: individuals

Market Dominance, Crime, and Globalisation - Messner, Steven F.; Rosenfeld, Richard (Social Dynamics of Crime and Control: New Theories for a World in Transition, 2000)
KM: Our point of departure is Karl Polanyi's classic work on the emergence of industrial capitalism and recent studies that further develop Polanyi's insights. We draw on these analyses to pose a fundamental issue confronting all capitalist societies: the need to restrain the market and prevent the economy from dominating other institutional realms. We explain how this general institutional challenge bear specifically on the problem of crime and crime control
Keywords: crime; double movement; globalization; institutional-anomie theory; law

Naukratis: Trade in Archaic Greece - Möller, Astrid (Oxford University Press, 2000)
Archaic Naukratis was a busy trading place in the Western Delta of the Nile, renowned for its sanctuaries and courtesans, granting the Greeks access to Egyptian grain and luxury items. Now, more than one hundred years after the discovery and excavation of Naukratis, the author offers the first full-length analysis of the archaeology and archaic history of this important site. Although Naukratis always features in modern accounts of ancient Greek colonization, it was not a place where the Greeks could freely establish their own political and social organization--it was under the strict control of the Egyptian pharaoh and his officials. To understand the special status of Naukratis, the author takes the port of trade model, surveying the political, social, and economic background of both Late Period Egypt and archaic Greece. A major section of the book comprises an archaeological re-evaluation of the topography of archaic Naukratis and its material finds. The sanctuaries, archaic pottery styles, terracottas, faiences, statuettes, and other small finds are examined in the light of recent scholarship, and an in-depth study of the literary evidence is brought to bear on the archaeological material. This book comprises a significant contribution to our understanding of Graeco-Egyptian relations during the seventh and sixth centuries BC and also demonstrates that Polanyian economic theory can play an invaluable rï¿½le in the ongoing debate about the concepts best employed to analyse the ancient Greek economy.
Keywords: Ancient Egypt; business & economics; economic history; history

Freedom and the Market (An Analysis of the Anti-globalization Movement from the Perspective of the Theoretical Foundation of the Evaluation of the Dynamics of Capitalism by Polanyi, Hayek and Keynes.) - Nikitin, Pavel V.; Elliott, John E. (Forum for Social Economics, 2000)
Those who believe that the free market is positively related to both economic efficiency and individual freedom are prone to regard resistance to the establishment of the global market essentially free from any serious sociopolitical constraint as a politically insignificant expression of impatience, ignorance, and hypocrisy. This article attempts to endow the manifestation of discontent with the status quo evident in public protests in Seattle and Washington DC with political significance through explicating it as an expression of a fundamental conflict between economic efficiency and individual freedom inherent in the global implementation of the principle of self-regulating markets. This analysis of the anti-globalization movement is conducted from the perspective of the theoretical foundation of the evaluation of the dynamics of capitalism by Polanyi, Hayek, and Keynes, and its conclusions are brought to bear upon the validity of their contesting views of the relationship between economic efficiency and individual freedom.
Keywords: anti-globalization movement; capitalist systems; international economic order; political economy

Karl Polanyi's Forms of Integration as Ways of Mapping - Schaniel, William C.; Neale, Walter C. (Journal of Economic Issues, 2000)
Researcher Karl Polanyi's "forms of integration"--redistribution, reciprocity, and exchange--have been much used to describe and explain various economies. Such mapping presents information about the sources and destinations of the flows of material means in each society in ways that are easily correlated with the variables that most thoroughly and simply account for the flows of material means in different societies. Mapping may be looked upon as the selection of a "projection" for portraying the flows of material means. The diagrams below illustrate the discussions of each form of integration and are examples of mapping. As is the case for projections selected for geographical mapping, for each way of mapping a form of integration the criterion of the appropriateness of the choice of projection is analogous to a mathematical function. The independent variables would be information about the social system; the dependent variable would be the directions in which the material means flow. The merits of the choice of projection are simplicity and the accuracy with which the directions of flow are portrayed.
Keywords: commercial policy; economics; forms of integration; functions; mappings (mathematics); mathematics; social sciences